Survey on an Intrusion Detection Systems Within Cloud Environment - ALi, Montather Ghalib; Alwi, Fadl Mutaher Ba; Gaphari, Ghaleb H. Al (International Journal of Computer Sciences and Engineering, 2021)
he decentralized nature of cloud computing paradigms has resulted class computing which prone to cyber- attacks and intrusions. One of major security matters in cloud is conducting intruder detection approaches for detecting and preventing network intrusions. The aim of this research paper is to review and analyze the research domain of collaborative, cooperative and distributed intrusion detection approaches within cloud environment. The research paper focusses on articles related to the keywords: cooperative, distributed, collaborative and their variations in three major databases, namely ScienceDirect, Springer Nature and the Institute of Electrical and Electronics Engineers‘ Xplore. Such databases are sufficiently cover the literature techniques related to the aforementioned keywords. The collected dataset consists of 23 articles, the largest proportion of them focuses on model‘s development that leverage collaborative intruder detection approaches, while the rest presents frameworks for intruder detection approaches. This study presents real analyses performed on available work: models, framework limitations and motivations. The study also, specifies the gap of the most state of the art related to cooperative and provides an extensive resource background for researchers who are interested in enhancing the performance of CIDSs within cloud environment. Finally, the paper suggests a new ensemble deep learning based model for improving the performance of proactive multi-cloud cooperative intrusion detection system.